Art therapy in Alzheimer’s disease. An opportunity of collaboration between intersectoral public and private organizations in the co-design of health and social care services - Giusti, Martina; Persiani, Niccolò (Frontiers in Psychiatry, 2023)
The WHO has recognized art therapy as effective support in the maintenance and in the restore of the mental health. In the last years, art therapy has been integrated into the assistance pathways of older people affected by neurocognitive disorders according to the demonstrated benefits as no conflicts with complement pharmacologic treatments and promotion of mental well-being thought the reduction of anxiety and stress. The shortage of organizational, economic, and professional resources in social-health public organizations does not allow to guarantee the provision of these services without the help of the private ones, not exclusively of social-health sector. This research aims to investigate how the collaboration between public and private organizations of different sector in the co-provision of non-pharmacological approaches guarantees the economic sustainability and the quality improvement of the services over time. The Alzheimer Café of Prato was selected as significant case study. Here art therapy programs into the taking care of older people in the first stages of the Alzheimer disease are developed, planned, supplied, and managed during the years due to the integration of the resources, ideas, and professionals provided both by public and private, social-health sector and cultural organizations. Economic sustainability and quality improvement of art therapy programs pass though the beginning of co-funding and co-planning projects, as an art therapy program, in which all organizations engaged in the peer-to-peer collaboration are coresponsible of the achievement of fixed results.